Education and Career Advancement Opportunities in Polish and English Nursing-A Comparative Study of Intensive Care Unit Nurses - Ewelina Wasielewska; Piotr Kordel; Marcin Moskalewicz (MDPI AG, 2024)
The aim of this study was to comparatively investigate education, job, and professional development satisfaction among intensive care unit nurses in Poland and England. A total of 258 ICU nurses from both countries were interviewed (72 Polish nurses working in Poland and 186 of various national backgrounds in England, including 50 of Polish origin). We used an 11-item structured survey followed by an open-ended qualitative interview retrospectively coded for statistical analysis. Regardless of national origin, nurses in England report significantly higher education satisfaction, attributed to better theoretical knowledge gain but not to other dimensions (such as practical knowledge or personal satisfaction). They also express greater satisfaction with job conditions regarding professional development, a state-of-the-art work environment, teamwork, and finance. The UK system is also considered significantly superior in promotion opportunities and participation in post-graduation training. In conclusion, systemic factors play a crucial role in career satisfaction and advancement in nursing, with the British band system having a clear advantage over the Polish one.